2013
DOI: 10.1017/s1092852912000697
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in obsessive compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) has a profound impact with a high disease burden. In order to truly understand the scope of the effect OCD has on the patient population, one must take into account not only the relentless symptoms beleaguering the patients but also examine their overall ability to enjoy their life. Quality of life (QOL) assessments/improvements are becoming an increasingly important component of healthcare, especially in the mental health field. This review examines QOL in OCD, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 63 publications
(115 reference statements)
1
57
0
3
Order By: Relevance
“…Two systematic reviews have recently investigated the published literature on this issue. 100,101 Most studies have used clinical samples and compared several dimensions of quality of life in OCD and other psychiatric disorders, chronic physical disorders and the general population. Fewer studies have used non-selected samples in the community, 101,102 but these have confirmed that OCD, even in individuals living in the community who have not made contact with services, can have a detrimental effect on quality of life compared with the healthy population.…”
Section: Impact On Quality Of Life and Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Two systematic reviews have recently investigated the published literature on this issue. 100,101 Most studies have used clinical samples and compared several dimensions of quality of life in OCD and other psychiatric disorders, chronic physical disorders and the general population. Fewer studies have used non-selected samples in the community, 101,102 but these have confirmed that OCD, even in individuals living in the community who have not made contact with services, can have a detrimental effect on quality of life compared with the healthy population.…”
Section: Impact On Quality Of Life and Functioningmentioning
confidence: 99%
“…101 Some studies have investigated quality of life as a long-term outcome in RCTs of psychopharmacological or psychosocial interventions. 100 These studies have concluded that changes in quality of life can be quite delayed and certainly are not expected in the short term. In the psychopharmacology trials, these changes may become evident after 1 year of continuous treatment.…”
Section: Impact On Quality Of Life and Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies had already described a decrease in QoL in adults with OCD with an associated Depression. 23 Another study developed in children with Tourette syndrome analyzed the influence of ADHD and OCD as co-morbidities in QoL and also found that it was more impaired comparing with 'pure' disease. 24 These findings highlight the relevance of applying a treatment directed not only for the main diagnostic but also for the comorbidities and of assessing their influence in patients' QoL.…”
mentioning
confidence: 99%
“…De todos os transtornos mentais, o Transtorno Obsessivo-Compulsivo (TOC) foi considerado pela OMS como a 10ª causa de incapacidade no mundo [4][5][6] . O TOC é um transtorno caracterizado por ideias obsessivas e/ou por comportamentos compulsivos recorrentes e tem sido reconhecido por seu curso crônico e incapacitante 4 . Tais ideias e comportamentos perturbam muito e consomem tempo da vida do sujeito, interferindo ocupacional e socialmente.…”
Section: Introductionunclassified